WORDS AND THEIR MEANING IN LINGUISTICS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines the number of words in each language and the number of sounds or their grammatical rules. Also, the learned new language becomes part of the stylistic repertoire of the native speaker, as with dialects and styles, or a certain language is chosen in a certain situation, in a social environment, in relation to native speakers, their feelings of identity. A person who studies new words throughout his life, especially where new objects are discussed, new ideas with new terms appear, even new names are given to old subjects.